2012
DOI: 10.2527/jas.2011-3999
|View full text |Cite
|
Sign up to set email alerts
|

Carcass yield traits of kids from a complete diallel of Boer, Kiko, and Spanish meat goat breeds semi-intensively managed on humid subtropical pasture1,2

Abstract: Bucklings (n = 275) from a complete diallel of Boer, Kiko, and Spanish meat goats were slaughtered at 7 mo of age (4 mo postweaning) to evaluate genetic effects on carcass yield. Breed of sire did not affect (P > 0.05) live, carcass, and primal weights. Conversely, breed of dam was a consistently significant source of variation for carcass weight traits. Kiko dams produced kids with heavier (P < 0.05) live, carcass, and primal weights than Boer dams. Weights from Spanish dams were intermediate to Boer and Kiko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The good body morphology of Boer kids for meat production has also been highlighted by numerous authors [ 9 , 10 , 19 , 39 , 40 ], but with heavier kids than those used in the present experiment. For example, Browning et al [ 10 ] carried out a complete diallel crossbreeding of the Boer, Kiko and Spanish breeds and found that the best morphological conformation scores, both in live animals (25–26 kg) and in carcasses (10.1–10.8 kg), were assigned to the descendants of Boer males. The descendants of Boer females also received the best rating in live animals, although this did not translate into a better carcass conformation score.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The good body morphology of Boer kids for meat production has also been highlighted by numerous authors [ 9 , 10 , 19 , 39 , 40 ], but with heavier kids than those used in the present experiment. For example, Browning et al [ 10 ] carried out a complete diallel crossbreeding of the Boer, Kiko and Spanish breeds and found that the best morphological conformation scores, both in live animals (25–26 kg) and in carcasses (10.1–10.8 kg), were assigned to the descendants of Boer males. The descendants of Boer females also received the best rating in live animals, although this did not translate into a better carcass conformation score.…”
Section: Discussionsupporting
confidence: 76%
“…An alternative used to improve meat production in goats consists of crossing the local breed with Boer males, which is a breed that enjoys worldwide recognition for its excellent body conformation, rapid growth rate and good carcass quality [ 9 ]. In some large breeds, such as the Kiko, crossing with the Boer breed does not improve the growth of kids [ 10 ], but in the MG breed, Pérez-Baena et al [ 7 ] showed that crossbreeding improved birth weight, the survival of offspring and the growth and conversion rates of kids during lactation, so production costs are reduced. Consequently, these authors considered the crossbreeding of MG females with Boer males to be of interest for the production of suckling kids.…”
Section: Introductionmentioning
confidence: 99%
“…Under good pastoral conditions, growth rate of 0.240, 0.238, and 0.218 kg/day were recorded for single, twin, and triplets Boer kids raised in Namibia, respectively (Barry & Godke, 1997). Meanwhile, the ADG of Boer kids in pre-weaning was 116.9 g/day as reported by Browning and Leite-Browning (2011).…”
Section: Adgmentioning
confidence: 65%
“…Myotonic- and Savanna-sired kids had better ( P < 0.05) conformation scores than Kiko-sired kids ( Table 4 ). Previous work indicated that the Boer influence improved the conformation scores of kids when harvested at 7 mo of age compared with the Kiko and Spanish influence but did not improve objective measures of carcass yield ( Browning et al, 2012 ). Savanna and Boer are similar breeds from South Africa and it seems that they similarly improve subjective kid conformation scores.…”
Section: Resultsmentioning
confidence: 97%